The transformation of death services as muhammadiyah’s da‘wah strategy in south kalimantan: : A sociological and theological analysis - Agus Miswanto; Alfa Nejatullah Muthahhari (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2026)
This article examines funeral management and death-related services as a form of structural and cultural da‘wah strategy implemented by Muhammadiyah in South Kalimantan. The study is motivated by the strong public trust in Muhammadiyah’s funeral services, which are utilized not only by Muhammadiyah members but also by the wider community across ethnic and various social backgrounds. Employing a qualitative descriptive-analytical approach, this research integrates perspectives from the sociology of religion and Muhammadiyah’s social theology to analyze the practice of da‘wah bil ḥāl through death services. Data were collected through in-depth interviews, participant observation, and document analysis conducted at Al-Jihad Mosque in Banjarmasin, in the Hulu Sungai Tengah region, and within the operational activities of Lazismu ambulance services in South Kalimantan. The findings indicate that Muhammadiyah has successfully transformed funeral management from a domestic and traditional practice into a professional, standardized, and sharia-compliant public service. These death services not only provide psychological comfort for bereaved families but also function as an effective instrument of da‘wah in fostering public trust and social solidarity. For Dayak communities, Muhammadiyah’s funeral services serve as a socio-theological safety net that reduces the economic burden of customary death rituals and strengthens the sustainability of religious commitment among converts. This article concludes that da‘wah through funeral services represents a contextual and responsive model of Islamic propagation that aligns with the needs of contemporary society.